PENGGUNAAN MEDIA VIDEO ANIMASI PADA MATERI HAK DAN KEWAJIBAN DI SEKOLAH UNTUK MENINGKATKAN KEDISIPLINAN SISWA KELAS III SD MUHAMMADIYAH 02 PEMATANGSIANTAR - Windi Yanti; Romaida Karo-Karo; Agus Junsion Naibaho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effectiveness of animated video media on the subject of Rights and Obligations in improving the discipline of third-grade students at Muhammadiyah 02 Elementary School Pematangsiantar. Discipline is an important character to support effective learning, but in reality it is still low, indicated by students often being late, lacking focus, and not completing assignments on time. The study used a descriptive qualitative method with observation, interview, questionnaire, and documentation techniques. The research subjects were 23 students and one Civics teacher. The media used was the animated video "Our Rights and Obligations" which was broadcast on YouTube. The results of the study showed a significant improvement after the use of animated videos. Students were more orderly, aware of their responsibilities, and obeyed school rules. The questionnaire data showed a discipline score reaching 87.60% with a very good category. Teachers also confirmed that this media increased enthusiasm, facilitated understanding, and encouraged active student involvement. Thus, animated videos are effective for improving student discipline.